2016
DOI: 10.1051/0004-6361/201629202
|View full text |Cite
|
Sign up to set email alerts
|

3D NLTE analysis of the most iron-deficient star, SMSS0313-6708

Abstract: Context. Models of star formation in the early universe require a detailed understanding of accretion, fragmentation and radiative feedback in metal-free molecular clouds. Different simulations predict different initial mass functions of the first stars, ranging from predominantly low-mass (0.1−10 M ), to massive (10−100 M ), or even supermassive (100−1000 M ). The mass distribution of the first stars should lead to unique chemical imprints on the low-mass second and later generation metal-poor stars still in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(113 citation statements)
references
References 97 publications
8
104
0
Order By: Relevance
“…Our 3859.911Å result agrees with that of Bessell et al (2015), [Fe/H](LTE) < −7.80, who used the same line. Our 3608.859Å LTE value agrees with that of Nordlander et al (2017) within 0.1 dex (they report [Fe/H](1D,LTE) < −7.34). In NLTE, we determine an upper limit of [Fe/H](NLTE) < −6.52 from the 3608.859Å line, and [Fe/H](NLTE) < −6.72 from the resonance 3859.911Å.…”
Section: Stellar Atmospheric Parameterssupporting
confidence: 86%
See 2 more Smart Citations
“…Our 3859.911Å result agrees with that of Bessell et al (2015), [Fe/H](LTE) < −7.80, who used the same line. Our 3608.859Å LTE value agrees with that of Nordlander et al (2017) within 0.1 dex (they report [Fe/H](1D,LTE) < −7.34). In NLTE, we determine an upper limit of [Fe/H](NLTE) < −6.52 from the 3608.859Å line, and [Fe/H](NLTE) < −6.72 from the resonance 3859.911Å.…”
Section: Stellar Atmospheric Parameterssupporting
confidence: 86%
“…Our 1D, NLTE result is, however, 0.19 dex lower than their 3D, NLTE value. Overall, Nordlander et al (2017) report agreement between their 1D and 3D NLTE results which adds confidence to our result and the use of our NLTE method. As no Fe lines could be detected, we did not compute any NLTE stellar parameters but instead adopt the temperature, gravity and microturbulent velocity from Bessell et al (2015).…”
Section: Stellar Atmospheric Parameterssupporting
confidence: 85%
See 1 more Smart Citation
“…SMSS J031300.36-670839.3 (hereafter SMSS J0313-6708, Keller et al 2014), is the most iron-poor star identified at present, with [Fe/H] ≤ −6.53, (Nordlander et al 2017). Li, C, Mg and Ca have been measured and there are upper limits on several other elements.…”
Section: Introductionmentioning
confidence: 99%
“…We present the inferred orbital parameters from both analyses in Table 1. 4. DISCUSSION Our measurement of [Sr, Ba/H] ≈ −6 for 2MASS J151113.24-213003.0 is surpassed by only three ultrametal poor halo stars: BPS CS 22968-0014, BPS CS 22885-0096, and SMSS J031300.36-670839.3 Keller et al 2014;Bessell et al 2015;Nordlander et al 2017). The [Sr, Ba/Fe] ≈ −3 abundances we measured in 2MASS J151113.24-213003.0 are more than a factor of two smaller than any previous measurement for an extremely metal-poor star in the comprehensive Stellar Abundances for Galactic Archaeology (SAGA) Database (Suda et al 2008).…”
Section: Dynamicsmentioning
confidence: 69%